USP5 stabilizes YTHDF1 to control cancer immune surveillance through mTORC1-mediated phosphorylation - Na Shao; Lei Xi; Yangfan Lv; Muhammad Idris; Lin Zhang; Ya Cao; Jingyi Xiang; Xi Xu; Belinda X. Ong; Qiongyi Zhang; Xu Peng; Xiaoyan Yue; et al. (Nature Communications)
Abstract The N6-methyladenosine binding protein YTHDF1, often upregulated in cancer, promotes tumor growth and hinders immune checkpoint blockade treatment. A comprehensive understanding of the molecular mechanisms governing YTHDF1 protein stability is pivotal for enhancing clinical response rates and the effectiveness of immune checkpoint blockade in cancer patients. Here, we report that USP5 interacts with YTHDF1, stabilizing it by removing K11-linked polyubiquitination. Insulin activates mTORC1, phosphorylating USP5 and promoting its dimerization, which binds to and protects YTHDF1 from degradation. Conversely, the CUL7-FBXW8 E3 ligase promotes YTHDF1 degradation. Deficiency in YTHDF1 or USP5 increases PD-L1 expression and suppresses immune-related gene expression, facilitating immune evasion. Combining USP5 inhibition with anti-PD-L1 therapy enhances anti-tumor immunity, suggesting USP5 as a potential biomarker for patient stratification. This study reveals a ubiquitination-dependent regulation of YTHDF1, proposing USP5 inhibition alongside PD-(L)1 blockade as a promising cancer treatment strategy.